The Role of Brand Image, Place and Service Quality in Increasing Customer Satisfaction for Noodle Culinary in Jember - Ningfiat, Nafira Ainur; Atika, Nur; Setyowati, Agustina; Qomariah, Nurul; Thamrin, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Today's food business competition is required to have strategies that are able to attract and retain consumers for the sustainability of the company. This research aims to see the influence of brand image, location and service quality on customer satisfaction at Mie "GCN" Jember. The population of this research is all people who have bought Jember "GCN" Noodles. The sample size was determined at 30 respondents with the condition that n≥30 is a large sample and research can be carried out. The sampling technique used is purposive sampling with the criteria being those who have purchased twice. Primary data was collected through a questionnaire using a Likert scale model which has been tested for validity and reliability. The data analysis technique used is Path Analysis with multiple linear regression analysis tools. Simultaneous research results show that brand image, place and service quality do not have a positive effect on customer satisfaction. Partially, it can be seen that the brand image variable has no impact on customer satisfaction. The place variable has a positive and significant effect on customer satisfaction. Meanwhile, the service quality variable has no influence on customer satisfaction